Image Segmentation through Encapsulation of its Constituents - Montenegro Joo, Javier (2010)
An algorithm to carry out segmentation of binary images has been developed and applied to computer synthesized images. The algorithm is based on surrounding image elements with different wrappings or capsules, which afterwards are individually extracted. The proposed algorithm may be used in pattern recognition and also in industrial automatization, for instance, to calculate the area of objects in an image.